2014
DOI: 10.1136/jnnp-2013-306941
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for congenital hydrocephalus: a nationwide, register-based, cohort study

Abstract: The higher risk for isolated CHC in first-born children as well as behavioural aspects and comorbidities associated with maternal use of antidepressants, should be the targets for future research. Potential biological pathways by which antidepressants may cause hydrocephalus remain to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 17 publications
2
38
1
1
Order By: Relevance
“…The same cohort study assessed PPI use during pregnancy and found that the relative risk of CH in children with exposure to PPI use during the first trimester of gestation was 2.35 compared with unexposed children. 19 Nonetheless, this risk was comparable to that for syndromic CH. Hence, this finding is not considered significant.…”
Section: Studymentioning
confidence: 90%
See 4 more Smart Citations
“…The same cohort study assessed PPI use during pregnancy and found that the relative risk of CH in children with exposure to PPI use during the first trimester of gestation was 2.35 compared with unexposed children. 19 Nonetheless, this risk was comparable to that for syndromic CH. Hence, this finding is not considered significant.…”
Section: Studymentioning
confidence: 90%
“…27 In a second cohort study, maternal diabetes and preeclampsia were investigated as risk factors but these associations did not reach significance. 19 Furthermore, prepregnancy obesity had a statistically significant association with CH in a meta-analysis study (OR 1.68).…”
Section: Lifestyle-modifiable Maternal Pathologiesmentioning
confidence: 99%
See 3 more Smart Citations